2020
DOI: 10.1111/acv.12583
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing tropical conservation and ecology research with aquatic environmental DNA methods: an introduction for non‐environmental DNA specialists

Abstract: Biodiversity conservation is a worldwide concern and proper management of threatened species or communities depends on reliable and accurate data collection. Despite the broad utility of environmental DNA (eDNA) for conservation management and the necessity for appropriate biodiversity management in the tropics, eDNA-based research conducted in tropical regions so far comprises only a small proportion of the cumulative eDNA literature. To address the growing demand for rapid and reliable species and community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 97 publications
1
36
0
Order By: Relevance
“…The sensitivity, non-invasiveness, and cost-efficiency of environmental DNA (eDNA) based methods have been proven for diverse habitats and species making them powerful new tools for conservation biology and biodiversity assessments (Barnes and Turner, 2016;Deiner et al, 2017;Huerlimann et al, 2020). Regarding the detection of fish species, eDNA-based monitoring outperforms traditional methods such as electrofishing: for example, for the detection of the endangered European weather loach, Misgurnus fossilis (Sigsgaard et al, 2015), the assessment of fish communities in Australian streams (McColl-Gausden et al, 2020), and the distribution of brook trout, Salvelinus fontinalis in a US watershed (Evans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity, non-invasiveness, and cost-efficiency of environmental DNA (eDNA) based methods have been proven for diverse habitats and species making them powerful new tools for conservation biology and biodiversity assessments (Barnes and Turner, 2016;Deiner et al, 2017;Huerlimann et al, 2020). Regarding the detection of fish species, eDNA-based monitoring outperforms traditional methods such as electrofishing: for example, for the detection of the endangered European weather loach, Misgurnus fossilis (Sigsgaard et al, 2015), the assessment of fish communities in Australian streams (McColl-Gausden et al, 2020), and the distribution of brook trout, Salvelinus fontinalis in a US watershed (Evans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences are then taxonomically assigned using a genetic reference database, which provides an integrative inventory of species and composition in aquatic systems (Deiner et al., 2017; Harrison et al., 2019). A recent synthesis counted 54 papers on tropical eDNA, whereas only 15 focused on marine systems (Bakker et al., 2019; Huerlimann et al., 2020; Sigsgaard et al., 2019; West et al., 2020). Compared to freshwater systems, the marine environment has a larger water volume to fish biomass ratio, the movement of molecules in suspension is influenced by various currents, and reef systems can contain up to hundreds of species, which might challenge the detection of individual species (Collins et al., 2019; Hansen et al., 2018; Harrison et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical ecosystems have historically been underrepresented in research (Collen et al., 2008), and increased monitoring efforts in these regions are urgently needed, particularly under ongoing global change (Barlow et al., 2018). Different abiotic conditions and high species richness might challenge the application of eDNA in the tropics (Huerlimann et al., 2020; Jerde et al., 2019). Studies of eDNA on coral reefs have shown a strong potential for biodiversity detection (Nguyen et al., 2020; Sigsgaard et al., 2019; West et al., 2020), but the scope of methodological testing remains narrow.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity, non-invasiveness and cost-efficiency of environmental DNA (eDNA) based methods has been proven for diverse habitats and species making them powerful new tools for conservation biology and biodiversity assessments (Barnes and Turner, 2016; Deiner et al, 2017; Huerlimann et al, 2020). Regarding the detection of fish species, eDNA-based monitoring outperforms traditional methods such as electrofishing: for example, for the detection of the endangered European weather loach, Misgurnus fossilis (Sigsgaard et al, 2015), the assessment of fish communities in Australian streams (McColl‐Gausden et al, 2020), and the distribution of brook trout, Salvelinus fontinalis in a US watershed (Evans et al, 2017).…”
Section: Introductionmentioning
confidence: 99%